2021
DOI: 10.1038/s41467-021-27288-3
|View full text |Cite
|
Sign up to set email alerts
|

The barley immune receptor Mla recognizes multiple pathogens and contributes to host range dynamics

Abstract: Crop losses caused by plant pathogens are a primary threat to stable food production. Stripe rust (Puccinia striiformis) is a fungal pathogen of cereal crops that causes significant, persistent yield loss. Stripe rust exhibits host species specificity, with lineages that have adapted to infect wheat and barley. While wheat stripe rust and barley stripe rust are commonly restricted to their corresponding hosts, the genes underlying this host specificity remain unknown. Here, we show that three resistance genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 102 publications
0
47
0
Order By: Relevance
“…This host specialization shows evidence of durability, as Pst has been endemic for over 60 years in Australia, but has not undergone a host jump to barley despite both crops being grown in the same regions (26). Screening of diverse barley accessions has found that Pst is capable of infecting and reproducing on a small subset of barley accessions: primarily landraces and wild barley, as well as the hypersusceptible accession SusPtrit (27). Using a diverse panel of barley accessions, we previously identified three R gene loci designated Rps6, Rps7, and Rps8 as contributing to the nonadapted status of barley to Pst (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This host specialization shows evidence of durability, as Pst has been endemic for over 60 years in Australia, but has not undergone a host jump to barley despite both crops being grown in the same regions (26). Screening of diverse barley accessions has found that Pst is capable of infecting and reproducing on a small subset of barley accessions: primarily landraces and wild barley, as well as the hypersusceptible accession SusPtrit (27). Using a diverse panel of barley accessions, we previously identified three R gene loci designated Rps6, Rps7, and Rps8 as contributing to the nonadapted status of barley to Pst (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Using a diverse panel of barley accessions, we previously identified three R gene loci designated Rps6, Rps7, and Rps8 as contributing to the nonadapted status of barley to Pst (27)(28)(29). Rps8 was mapped to the long arm of chromosome 4H using a mapping population derived from SusPtrit × Golden Promise (SxGP) (27,30). In this work, we fine-mapped Rps8 to a 936-kb locus on chromosome 4H, which encompasses a presence/ absence variation across barley accessions.…”
Section: Introductionmentioning
confidence: 99%
“…Typically the plants are entirely immune against the non-adapted pathogens, e.g., barley is immune to Bgt and wheat to Bgh. However, some plant genotypes may allow microscopic growth of non-adapted pathogens, known as cryptic infection (Romero et al, 2018;Bourras et al, 2019;Bettgenhaeuser et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Typically the plants are entirely immune against the non-adapted pathogens, e.g., barley is immune to Bgt and wheat to Bgh. However, some plant genotypes may allow microscopic growth of non-adapted pathogens, known as cryptic infection (Romero et al ., 2018; Bourras et al ., 2019; Bettgenhaeuser et al ., 2021). The barley/wheat-powdery mildew model provides several advantages to the researchers: the fungus growth is fast and highly synchronized, the majority of the fungal biomass is located on the leaf surface, with straightforward to observe structures.…”
Section: Introductionmentioning
confidence: 99%
“…The primary importance of resistance genes is protecting barley against powdery mildew. However, their postulation has many other applications, including: (1) mapping the distribution of native resistance worldwide [ 13 , 14 , 15 ]; (2) the selection of genetic resources for crop breeding [ 16 , 17 ]; (3) the selection of well-characterized genotypes for evaluating partial resistance [ 18 ]; (4) assessing efficacy and expected durability of resistance of varieties including potential candidates for registration [ 19 ]; (5) description of new resistance in registered varieties [ 20 ]; (6) identifying varieties and confirming their authenticity and pedigrees [ 21 ]; (7) selection of differential varieties for studying pathogen populations [ 22 ] and their evolution [ 23 ]; (8) uncovering genotypic contamination [ 24 ]; and (9) basic research including the effect of Ml alleles on resistance to other pathogens [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%